Efektivitas Penerapan SiMBA Dalam Pengelolaan Zakat, Infak, Dan Sedekah Di BAZNAS Kabupaten Gresik - Ridhotul Khafshoh Islami; Ananta Prathama (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research aims to describe the effectiveness of the application of the Information Management System of the National Zakat Agency (SiMBA) in managing zakat, infak, and sedekah in BAZNAS Kabupaten Gresik. This research method uses a descriptive qualitative method. The data collection techniques used in this research are observation, interviews, and documentation. Referring to the theory of effectiveness according to Lubis and Huseini, the results show that: (1) The resource approach: human resources consist of three employees as active and compact SiMBA operators. Infrastructure is supported by three computer devices and internet networks. However, the computer specifications are not yet optimal and internet network issues are still a problem. (2) The process approach: the mechanism of ZIS management runs smoothly supported by complete and easy-to-use SiMBA features. (3) The goals approach: has shown aspects of transparency and accountability seen from good financial reports that are published on the BAZNAS Gresik website, as well as the existence of digital notifications and receipts that will be received by muzaki after paying zakat. Based on the research results, it can be conclude that the implementation of SiMBA in managing zakat, infak, and sedekah in BAZNAS Kabupaten Gresik has been effective.